A recorribilidade das sentenças arbitrais administrativas, a partir de um estudo comparado entre os ordenamentos jurídicos luso-brasileiro - Manfrin, Aline Pereira (2023)
A comparative Luso-Brazilian law analysis is carried out, with the purpose of verifying whether the distinctive features of administrative arbitration, established by the public legal regime, justify the control by the State by the appeal of the arbitral sentence. After introducing the concept of arbitration, the introduction contextualizes the institutes' history in Ancient Greece and Imperial Rome, showing that arbitration has always been present in different civilizations before the State and its institutions. Subsequently, it shows the appearance of this method of conflict resolution from the Portuguese perspective until 2011 with the arrival of the Voluntary Arbitration Law, Law n. 63/2011. Then it looks at the Brazilian scene until the Arbitration Law, Law n. 9.307/1996, was approved and changed in 2015 by Law n. 13.129/2015. After these reflections, it continues with the study of the evolution of Arbitration in the public sphere, with the aim of identifying the characteristics of administrative arbitration. In Portugal, the milestone was the administrative reform of 2002/2004, which approved the Code of Procedure in Administrative Courts, Law n. 15/2002, altered by the Decree-Law n. 214-G/2015 and Law n. 118/2019. In 2015, the legislator extended the field of arbitrable subjects and in 2019, in a legislative contradiction, removed the rule of finality of the arbitral award, provided by the Voluntary Arbitration Law, article 39, n. 4, for the administrative arbitral award. The Institute's progress in the Brazilian public administration, regulated by the Private Arbitration Law, was then shown, which initially faced obstacles in its implementation. The mentality changed with the progress and acceptance of arbitration, culminating in the reform of the Brazilian Arbitration Law, by the Law n. 13.129/2015. Accordingly, to discuss the subject of this research, the appeal system provided by the Code of Procedure in Administrative Courts is analyzed in more detail. It indicates that the Brazilian Arbitration Law keeps the rule that the arbitral award cannot be appealed. Then, a comparison is made between the appeal system provided by the Code of Procedure in Administrative Courts and what has been defended by the doctrine and jurisprudence regarding the appealability of the administrative arbitral award in the Brazilian Arbitration Law. Based on these findings, the appeal system provided by the Code of Procedure in Administrative Courts is analyzed in more detail. Finally, a comparison is made between the appeal system provided by the Code of Procedure in Administrative Courts and the doctrine and jurisprudence regarding the appealability of the administrative arbitral award in the Brazilian Arbitration Law.